"Dance Therapy" as a psychotherapeutic movement intervention in Parkinson's disease. (October 2018) - Michels, Kristi; Dubaz, Ornella; Hornthal, Erica; Bega, Danny
Highlights: Dance therapy is the psychotherapeutic use of movement to improve physical, emotional, cognitive, and social wellbeing. 13 subjects with PD were randomized 2:1 to dance therapy or support group control. All participants in dance therapy enjoyed the classes and most felt they were beneficial. Pre-determined feasibility goals were met. Clinical outcomes were explored and warrant further study in a powered study with groups matched for disease severity. Abstract: Background: Previous studies in Parkinson's Disease (PD) have described benefits of dance for motor and non-motor outcomes, yet few studies specifically look at Dance Therapy (DT) as a specific psychotherapeutic model for PD. DT is the psychotherapeutic use of movement to improve physical, emotional, cognitive, and social integration and wellbeing. Objective: 1) Explore the safety and feasibility of a 10-week DT program for PD. 2) Collect pilot data on efficacy of DT. Design/Methods: Prospective, randomized-controlled study in subjects with PD. 13 participants randomized 2:1 to DT (n = 9) or support group (n = 4). Assessments were completed 1–2 weeks prior to the first session and after the final session, and included attendance, Hoehn and Yahr Scale (H&Y), Unified Parkinson's Disease Rating Scale (MDS-UPDRS), Montreal Cognitive Assessment, Timed Up and Go, Berg Balance Scale, Beck Depression Inventory, Fatigue Severity Scale, Visual Analog Fatigue Scale, Parkinson's Disease Questionnaire-39, and an exit satisfaction survey. Results: All participants completed the study. The control group was older and had a higher mean baseline MDS-UPDRS III score (27.56 dance vs. 40.75 control) and H&Y score (2.11 dance vs. 2.50 control). 7 of 9 in DT and all control subjects attended at least 70% of classes. All participants in DT enjoyed the classes and most felt they were beneficial. The greatest improvement in motor measures was in MDS-UPDRS III (−4.12 (dance) vs. −1.75 (control)). Non-motor outcomes were explored as well. Conclusions: DT is introduced as an enjoyable mind-body intervention for PD. Further studies powered for efficacy and with groups matched for disease severity are warranted.